(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: In recurrent uveitis, establishing whether any herpetic infection has played an etiological or triggering role in the disease is important for selecting the appropriate treatment. Purpose: To assess the results of complex enzyme immunoassay testing (CEIAT) performed for patients with both uveitis and herpes simplex virus (HSV) infection in the process of treatment. Materials and Methods: In 73 uveitis patients, the CEIAT was used to determine serum levels of anti?HSV-IgМ and anti?HSV-IgG antibodies (Ab) to herpes simplex virus type 1 and type 2 (HSV1&2), IgG class Ab to nonstructural early viral antigens of HSV1&2, and the avidity of specific IgG Ab to HSV1&2. Results: The most common etiology of uveitis was herpetic infection (25.7%). In 74.3% of cases, HSV played a triggering role. The following three types of specific immunity were registered: (1) significantly (р<0.01) increased levels of anti-HSV IgM and anti?HSV-IgG Ab and IgG class Ab to nonstructural early viral antigens, with the avidity index (AI) values exceeding 50% (27 patients), (2) the most increased (р<0.001) levels of anti?HSV-IgG Ab and IgG class Ab to nonstructural early viral antigens, with the AI values exceeding 50% (35 patients), and (3) only the level of IgG class Ab to nonstructural early viral antigens is slightly increased (р<0.05), with high AI values (12 patients). The third type of immune response was as a manifestation of the immune tolerance of the human body, with the most clinically severe course of the inflammatory process. Conclusion: In uveitis in the presence of HSV infection, the results of the CEIAT provide the practitioner an opportunity to investigate the activity of inflammatory process and define a pathogenetically sound scheme to correct the alterations revealed.